Rice bran arabinoxylan compound as a natural product for cancer treatment - an evidence-based assessment of the effects and mechanisms - Soo Liang Ooi; Peter S. Micalos; Jeanman Kim; Sok Cheon Pak (Taylor & Francis Group, 2024)
AbstractContext Rice bran arabinoxylan compound (RBAC) is a natural immunomodulator with anticancer properties.Objective This study critically evaluates the available evidence on the biological pathways of RBAC and its effects on cancer treatment.Methods This secondary analysis of a scoping review includes studies evaluating the mechanisms of RBAC on healthy or malignant cells, animal models, or humans for cancer prevention or treatment. Data from randomized controlled trials on survival and quality of life outcomes were subjectd to meta analysis.Results The evidence synthesis was based on 38 articles. RBAC exhibited antitumor properties by promoting apoptosis and restoring immune function in cancer patients to enhance inflammatory and cytotoxic responses to block tumorigenesis. RBAC works synergistically with chemotherapeutic agents by upregulating drug transport. In a clinical trial, combining RBAC with chemoembolization in treating liver cancer showed improved response, reduced recurrence rates, and prolonged survival. RBAC also augments the endogenous antioxidant system to prevent oxidative stress and protect against radiation side effects. In addition, RBAC has chemoprotective effects. Animals and humans have exhibited reduced toxicity and side effects from chemotherapy. Meta analysis indicates that RBAC treatment increases the survival odds by 4.02-times (95% CI: 1.67, 9.69) in the first year and 2.89-times (95% CI: 1.56, 5.35) in the second year.Conclusion RBAC is a natural product with immense potential in cancer treatment. Additional research is needed to characterize, quantify, and standardize the active ingredients in RBAC responsible for the anticancer effects. More well-designed, large-scale clinical trials are required to substantiate the treatment efficacies further.